Intellectual Capital's contribution to increasing competitive advantage - Handayani, Sri; Karnawati, Yosevin; H S, Darmansyah (International Journal of Psychosocial Rehabilitation, 2020)
Intellectual capital is an intangible asset that may provide the company with a competitive advantage. Intellectual capital is difficult to understand, but if it is discovered and explored and developed it will be beneficial to be able to compete in its industry. The paper seeks to estimate and analyze the intellectual capital factor, which consists of value-added capital coefficient, human capital, and structural capital toward competitive advantage. The design of this research is explanatory causal. Population in this study are mining companies on the Indonesia Stock Exchange in 2016 to 2018. The sampling technique of this study was saturated sampling with a total of 223 data. Data analysis techniques using multiple linear regression. The results of the study explained that the coefficients of value-added capital, human capital, and structural capital simultaneously influence competitive advantage. Partially the coefficient of added value of capital and structural capital has a positive effect on competitive advantage. However, human capital does not affect competitive advantage. The results of this research are in accordance with resource-based theory in which intellectual capital is able to act as a unique resource to create competitive advantage for companies because it is able to provide added value to the company.